Evaluation of the Immune Response Induced by CoronaVac 28-Day Schedule Vaccination in a Healthy Population Group - Escobar, Alejandro; Reyes-López, Felipe E.; Acevedo, Mónica L.; Alonso-Palomares, Luis; Valiente-Echeverría, Fernando; Soto-Rifo, Ricardo; Portillo, Hugo; Gatica, Jimena; Flores, Ivan; Nova-Lamperti, Estefanía; Barrera-Avalos, Carlos; Bono, María Rosa; et al. (Frontiers in Immunology, 2022)
CoronaVac vaccine from Sinovac Life Science is currently being used in several countries. In Chile, the effectiveness of preventing hospitalization is higher than 80% with a vaccination schedule. However, to date, there are no data about immune response induction or specific memory. For this reason, we recruited 15 volunteers without previous suspected/diagnosed COVID-19 and with negative PCR over time to evaluate the immune response to CoronaVac 28 and 90 days after the second immunization (dpi). The CoronaVac administration induces total and neutralizing anti-spike antibodies in all vaccinated volunteers at 28 and 90 dpi. Furthermore, using ELISpot analysis to assay cellular immune responses against SARS-CoV-2 spike protein, we found an increase in IFN-gamma- and Granzyme B-producing cells in vaccinated volunteers at 28 and 90 dpi. Together, our results indicate that CoronaVac induces a robust humoral immune response and cellular immune memory of at least 90 dpi.